2014
DOI: 10.1002/jmv.23951
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HBV, HDV, HCV, and HIV infection during pregnancy in northern Benin

Abstract: Pregnant women are not screened for HBsAg and anti-HCV antibodies in many African countries. As there are few data concerning the prevalence of HBV, HDV, and HCV serological markers in Benin, the aim of this study was to evaluate their 2011 prevalence in pregnant women undergoing HIV screening in a rural area of north Benin, and compare the data with those reported for the same area in 1986. The sera of 283 women were examined for HBsAg, anti-HBs, anti-HBc, anti-HCV, and anti-HIV 1/2 antibodies. In the case of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 32 publications
5
32
2
4
Order By: Relevance
“…In other studies elsewhere in Africa, prevalence varied from 0-50% was reported without any clear explanation on these variations [12][13][14]. In two previous studies carried out in the northern part of Benin, Zanchetta et al [7] reported 19.4% prevalence rate for anti-HDV antibodies while a rate of 11.4% was reported by de Paschale et al some years later [8]. These findings were higher than what was found in the present study.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In other studies elsewhere in Africa, prevalence varied from 0-50% was reported without any clear explanation on these variations [12][13][14]. In two previous studies carried out in the northern part of Benin, Zanchetta et al [7] reported 19.4% prevalence rate for anti-HDV antibodies while a rate of 11.4% was reported by de Paschale et al some years later [8]. These findings were higher than what was found in the present study.…”
Section: Discussioncontrasting
confidence: 71%
“…In Benin, data on co-infection with HDV, HCV and HIV in HBV infected patients are rare. To our knowledge, the only two published studies on co-infection with these viruses were on a limited number of patients in one hospital in the Northern part of the country [7,8]. We aimed in the present study to assess the prevalence of HDV, HCV and HIV infections in patients chronically infected with HBV in Cotonou, the largest city in Benin.…”
mentioning
confidence: 99%
“…Particularly, African HDV genotypes (i.e., HDV-1 and HDV-5 to -8) are poorly quantified by almost all available assays and are either undetected or dramatically underestimated (11). These different genotypes originally had a specific geographic distribution; however, due to ancient or recent migrations of populations, this genetic variability is now encountered in different countries worldwide (9)(10)(11)(17)(18)(19)(20)(21)(22)(23)(24)(25). In this respect, France, where genotypes HDV-5 to -8 representing 20% of spreading strains were characterized, is an outstanding example (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The research begins to exist from the moment it is published, and the renewal of knowledge is driven by this socialization. In this sense, the scientific journals and, consequently, the scientific article itself play a fundamental role in achieving these aims (Curty and Boccato, 2005).…”
Section: Resultsmentioning
confidence: 99%